1990
DOI: 10.1115/1.2927694
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Partial Length Circular Pin Fins As Heat Transfer Augmentors for Airfoil Internal Cooling Passages

Abstract: Pin fins are commonly used as heat transfer augmentors for internal cooling of turbine airfoils. These pins may extend from one wall to the other or may be segmented to meet specific requirements of removing the airfoil’s varying heat load. Three configurations of the partial pins were tested in a channel with aspect ratio 25:1 and the results are compared with those for the full pins. The array average heat transfer rate decreases linearly with increasing gap and is bounded by the value for full pins at one e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…It has been demonstrated by various authors [23,24] that cylinders with streamline-shaped crosssection have much less flow resistance than circular ones, while they have about the same behavior in terms of heat transfer. The work in [10] also investigated the partial length circular pin fin concept and found that both the array averaged-heat transfer and friction factor decrease with increasing gap distance.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated by various authors [23,24] that cylinders with streamline-shaped crosssection have much less flow resistance than circular ones, while they have about the same behavior in terms of heat transfer. The work in [10] also investigated the partial length circular pin fin concept and found that both the array averaged-heat transfer and friction factor decrease with increasing gap distance.…”
Section: Introductionmentioning
confidence: 99%
“…Chyu [9] showed that pin fin fillets reduce heat transfer as compared to the nonfillet case. Arora and Abdel-Messeh [10] investigated the effects of partial length pin fins, as well. Another consideration involves the importance of maintaining heat transfer capacity deeper into an array of pin fins.…”
Section: Previous Studiesmentioning
confidence: 99%
“…A comparison of the various heat transfer augmentation techniques used in internal coolant passages, including pin fins, was performed by Ligrani et al [10]. Different pin fin shapes and concepts have been studied as alternatives to circular fins, for example, cube-and diamond-shaped pin fins [6], elliptical pin fins [21] and partial pins [2,5].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of half pins on the heat-transfer coefficient was studied by Arora and Abdel-Messeh [2]. The friction factor for different geometries of partial pins is lower for partial pins compared to full-length pins.…”
Section: Introductionmentioning
confidence: 99%